How to evaluate and improve a medical education programme - Gwyndaf Roberts; Rich Bregazzi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
The evaluation of any medical education programme is an important and continuous task. The information gathered will inform strategic decision making and programme improvement. Using an established and widely recognised evaluation model helps structure and support the process.